Band gap calculation and photo catalytic activity of rare earths doped rutile TiO2 - 边亮 宋绵新 周天亮 赵效勇 戴清清 (Journal of rare earths, 2009)
The density of states （DOS） of 17 kinds of rare earths （RE） doped rutile TiO2 was by using first-principles density functional theory （DFT） calculation. The band gap widths of RE doped futile TiO2 were important factors for altering their absorbing wavelengths. The results show that RE ions could obviously reduce the band gap widths and form of energy of ruffle TiO2 except Lu, Y, Yb and Sc, and the order of absorbing wavelengths of RE doped ruffle TiO2 were the same as that of the results of calculation. The ratio of RE dopant was another important factor for the photo catalytic ＇activity of RE doped rutile TiO2, and there was an optimal ratio of dopant. There was a constant for predigesting the calculation difficulty, respectively, which were 0.5mol.% and 100 mol^-1 under supposition. The band gap widths of RE doped rutile TiOz by DFT calculation were much larger than that by experiment. Finally, by transferring the calculation values to experiment values, it could be found and predicted that RE enlarged obviously the absorbing wavelengh of ruffle TiO2. In addition, the degree of RE ions edging out the Ti atom using the parameters of RE dements was computed.